1998
DOI: 10.1046/j.1365-2559.1998.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial mediterranean fever and acute myocardial infarction secondary to coronary vasculitis

Abstract: The histopathological findings of the vasculitis were not in keeping with PAN. We postulated that the pathogenesis of vasculitis in FMF is different from that of the classic PAN and might be similar to the mechanism of the serosal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Importantly, recent studies with cardiovascular imaging techniques identified signs of diastolic dysfunction and microvascular coronary pathology which were correlated with elevated levels of CRP during attack-free period [31,32]. Clinical significance of coronary pathology in FMF was also highlighted in a few previous reports of coronary vasculitis, transient left bundle branch block and MI associated with inflammation in FMF [33][34][35].…”
Section: Fmf As a Low-grade Inflammatory Disordermentioning
confidence: 91%
“…Importantly, recent studies with cardiovascular imaging techniques identified signs of diastolic dysfunction and microvascular coronary pathology which were correlated with elevated levels of CRP during attack-free period [31,32]. Clinical significance of coronary pathology in FMF was also highlighted in a few previous reports of coronary vasculitis, transient left bundle branch block and MI associated with inflammation in FMF [33][34][35].…”
Section: Fmf As a Low-grade Inflammatory Disordermentioning
confidence: 91%
“…Furthermore, over the past few years, several reports have been published, linking subclinical inflammation with hypercoagulopathy and thrombosis in FMF [46][47][48][49][50][51]. It has been reported that persistent inflammation in FMF might cause coronary vasculitis, transient left bundle branch block, and MI [52,53]. Interestingly, thrombosis of the cerebral arteries causing stroke was also reported in a patient with FMF having M694V homozygosity and extremely high acute phase response [49].…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 99%
“…We found 2 case reports of myocardial infarction occurring in patients with FMF [ 21 , 22 ]. A third case is included in a study on aetiology of acute corornary syndrome under the age of 30 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%